Phosphoinositides in membrane contact sites. (11th April 2016) - Raiborg, Camilla; Wenzel, Eva M.; Pedersen, Nina M.; Stenmark, Harald
Abstract : Cellular membranes communicate extensively via contact sites that form between two membranes. Such sites allow exchange of specific ions, lipids or proteins between two compartments without content mixing, thereby preserving organellar architecture during the transfer process. Even though the molecular compositions of membrane contact sites are diverse, it is striking that several of these sites, including contact sites between the endoplasmic reticulum (ER) and endosomes, Golgi and the plasma membrane (PM), and contact sites between lysosomes and peroxisomes, contain phosphorylated derivatives of phosphatidylinositol known as phosphoinositides. In this mini-review we discuss the involvement and functions of phosphoinositides in membrane contact sites.